Students' Perspectives on their ideal English professor in class (Research, Society and Development, 2024)
This research aims to identify students' perspectives on their ideal English professor, characteristics and skills and investigate whether they would like to learn a second language and consider it to aid their professional life. Therefore, a survey was done online with  N= 220 learners taking the A1 English level in a public university in the coastal region of Ecuador. The data collected comprised 19 statements divided into three categories  ( 1. The perspective in the English professor's Identity; (2. Perspectives on the English Professor's Instruction; (3. Teachers Profile. The analysis uses descriptive statistics. The results demonstrate that students prefer flexible English professors who motivate them to learn a second language, which is essential for them. Most of the students agree that the ideal English professor must have a good proficiency in English level and studied in the field. In summary, as students like to learn a second language, believing it is essential for their professional career, they would prefer a professor who adapts to their necessities.